In Silico Studies: Virtual Screening Of The Compound Of Sea Fan (Gorgonia Mariae) As Antiasthmatic - Mustarichie, Resmi; Kelutur, Faruk Jayanto (Asian Journal of Pharmaceutical Research and Development, 2021)
Sterol is a secondary metabolites for a group of steroids that can treat a disease caused by synergistic effect between compound of metabolite with polyvalent activity. Sea fan (G. mariae) has a major compound (sterol) that has been used by the society of Maluku, Indonesia as an asthma substance but needs research done because it has not been reported widely and only empirical data from the society. For that, virtual screening is a necessary using the in silico method as a first step in determining the effectiveness and predicting the value of free energy bonding (ΔG), inhibition contents (Ki), interaction of amino acid residue using Autodock Tools 4.2, Lipinski Rule of Five and pre-ADMET in determining absorption, distribution and toxicity. The result showed that 24-methyl cholesterol had a value of ΔG (-9.98 kcal/mol) and Ki (48.26 nM), where the value of ΔG were smaller than salmeterol as a comparative drug. Prediction of oral drug candidate is a not eligible because the of Log P should not be >5 (Log P = 7.635). The value of absorption (HIA = 100% ; Caco-2 = 51.404 nm sec-1) and toxicity (there are no risk of mutagenic and carcinogenic). Thus, compound of the 24-methyl cholesterol from G. mariae are potentially as asthma medications but cannot be administered oral.